Konsumsi Nutrien Profil dan Metabolit Darah Induk Domba dengan Ransum Kaya Lemak Asal Minyak Nabati: Nutritional Intake, Blood Profile and Metabolites in Ewes Fed a Fat-Rich Diet of Vegetable Oils - L Khotijah; Nurmiasih Nurmiasih; D Diapari (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2020)
The aimed of this study was to evaluate the effect of vegetable fat supplementation in diet upon nutritional intake, the blood profile and metabolite of Garut ewes. Ten ewes with an initial weight of 24.87 ± 4.02 kg were used in this experiment. The feed composition and ingredients used were based on the feed commonly used by Garut sheep breeders. The Sunflower seed oil and canola oil were used as source of vegetables oils. The feeding treatments were R0 (control = without the addition of vegetable oils) and R1 (the ration contains 5% vegetable oil). The data obtained were analyzed by T-Test. Nutrient intakes, including dry matter (DM), Crude Protein (CP), Crude Fat (CF), Crude Fiber (CF) and Nitrogen-Free Extract (NFE) were similar between dietary treatment of 5% vegetable oils supplementation and control. While Fat consumption was significantly higher (p<0.01) in vegetable oil supplemented group (R1) compare to control. The results of blood metabolites, including glucose and cholesterol and blood profile (hematocrit, hemoglobin, leukocytes, erythrocytes) analysis indicate that vegetable oil supplementation can be done without any significant effect. It was concluded that the ration containing 5 percent vegetable oil was not interfere the nutrients consumption, blood profile and metabolite levels of the postpartum ewes, so it can be applied by farmers.